Uso de aluminato de estrôncio dopado com európio e disprósio como marcador luminescente para detecção de resíduos de disparo de arma de fogo - Tonin, Paulo Henrique (My University, 2025)
Forensic ballistics is a fundamental area of forensic science, dedicated to the analysis of evidence related to the use of firearms in criminal activities. Among the aspects investigated, the detection and characterization of gunshot residues stand out, as they can provide valuable information about the firearm used, the distance of the shot, and even the possible identity of the shooter. Traditional detection methods, such as spectroscopy and scanning electron microscopy (SEM), are widely used, but they present challenges related to sensitivity, cost, and accessibility of the analysis. In this context, the development of new approaches for marking and identifying these residues has become an area of growing interest in the scientific community. A promising solution involves the use of luminescent materials that can be visualized under specific lighting, facilitating field detection without the need for sophisticated equipment. Among these materials, lanthanide-doped aluminates have stood out due to their photoluminescent properties, thermal stability, and resistance to adverse environmental conditions. Thus, this study aimed to investigate the feasibility of using europium- and dysprosium-doped strontium aluminate as a luminescent marker for gunshot residues. To this end, the compound was initially characterized by Scanning Electron Microscopy coupled with Energy Dispersive X-ray Spectroscopy (SEM-EDS), laser diffraction, X-ray diffraction (XRD), and Thermogravimetric Analysis (TGA). Afterward, three concentrations of the marker (5%, 10%, and 15%) were tested to assess its effectiveness in detecting the residues. Based on the results, the marker showed an average particle size of 64.43 ?m, a monocyclic structure, and high stability at high temperatures. SEM-EDS analysis demonstrated the presence of the marker on the surfaces of interest, while UV illumination allowed clear visualization of the residue after the shots. The results indicate that the 15% concentration presents the best performance in terms of residue adhesion and persistence. Therefore, the findings of this study suggest that the tested compound may be a promising tool for forensic investigations, allowing rapid and accurate detection of gunshot residues. In parallel with this project, a review article was developed focusing on the main techniques for identifying gunshot residues. [resumo fornecido pelo autor]
A balística forense é uma área fundamental da ciência forense, dedicada à análise de evidências relacionadas ao uso de armas de fogo em atividades criminosas. Entre os aspectos investigados, destaca-se a detecção e caracterização dos resíduos de disparo, que podem fornecer informações valiosas sobre a arma utilizada, a distância do disparo e até mesmo a possível identidade do atirador. Métodos tradicionais de detecção, como espectroscopia e microscopia eletrônica de varredura, são amplamente empregados, mas apresentam desafios relacionados à sensibilidade, custo e acessibilidade das análises. Nesse sentido, o desenvolvimento de novas abordagens para a marcação e identificação desses resíduos tem sido um tema de crescente interesse na comunidade científica. Uma solução promissora envolve o uso de materiais luminescentes que possam ser visualizados sob iluminação específica, facilitando a detecção em campo sem a necessidade de equipamentos sofisticados. Dentre esses materiais, os aluminatos dopados com íons lantanídeos têm se destacado devido às suas propriedades fotoluminescentes, estabilidade térmica e resistência a condições ambientais adversas. Assim, este trabalho teve como objetivo principal investigar a viabilidade do uso de aluminato de estrôncio dopado com európio e disprósio como marcador luminescente para resíduos de disparo de armas de fogo. Para isso, inicialmente o composto foi caracterizado por Microscopia eletrônica de varredura acoplada a espectroscopia por dispersão em energia de raios-X (MEV-EDS), difração a laser, difração de Raios X (DRX) e análise termogravimétrica, após foram testadas três concentrações do marcador (5%, 10% e 15%) para avaliar sua eficácia na detecção dos resíduos. Com base nos resultados o marcador apresentou um tamanho médio de partícula de 64,43 ?m, uma estrutura monocíclica e alta estabilidade a altas temperaturas. As análises por MEV-EDS demonstraram a presença do marcador nas superfícies de interesse, enquanto a iluminação UV permitiu a visualização clara do resíduo após os disparos. Os resultados indicam que a concentração de 15% apresenta a melhor performance em termos de adesão e persistência dos resíduos. Assim, os resultados deste trabalho indicam que o composto testado pode ser uma ferramenta promissora para investigação forense, permitindo a detecção rápida e precisa de resíduos de disparo. Paralelamente a este projeto foi elaborado um artigo de revisão focado nas principais técnicas de identificação de resíduos de disparo de arma de fogo. [resumo fornecido pelo autor]
Keywords: Ciência dos materiais; Luminescência; Arma de fogo; Balística forense; Materials science; Luminescence; Firearms; Forensic ballistics